Information, knowledge and technology in the educational context - Watari, Angela Vicente Alonso; Francisco de Almeida Júnior, Oswaldo (Ciência da Informação em Revista, 2025)
Currently, the development of Digital Information and Communication Technologies (TDIC) is noto-rious for the evolution of all sectors of society. In the school context, technologies appear as an at-tractive means for information to be consolidated. Technological devices facilitate access and the acquisition of knowledge, but they are not decisive, since the mediation of information is funda-mental for the construction of knowledge. However, for information to become knowledge, it is necessary to understand, have a critical sense and make sense for the lives of individuals. In this sense, the study aims to discuss contributions of knowledge construction, appropriation of infor-mation and the use of digital information technologies (TDIC) for contemporary society, especially the educational context. With the development of a bibliographic review based on the production of researchers who develop studies on this theme, it was possible to elaborate the concepts of in-formation, knowledge and digital technologies and correlate them to the school context.